Analisis Butir Soal Pilihan Berganda Pada Training Teknisi Level 0 - Apprentice Tahun 2023 - Fery Irawan; Sutiman Sutiman (Journal of Automotive Technology and Education, 2026)
Abstract Item analysis is a process used to evaluate the quality of each test item to ensure that the questions effectively measure participants’ abilities. Based on observations at PT SGMW Motor Indonesia, item analysis for the Level 0 – Apprentice Technician Certification in 2023 had not been implemented, as indicated by the lack of attention to the difficulty level of the test items. This study employed a descriptive method with a quantitative approach, involving certification participants as the research subjects and the Level 0 – Apprentice certification test items as the objects. Data were collected through documentation and analyzed using Microsoft Excel to assess validity, reliability, item difficulty, discrimination index, and distractor effectiveness. The results show that out of 250 items analyzed, 34% (84 items) were rejected, 32% (80 items) required revision, and 34% (86 items) were accepted. These findings highlight the importance of conducting systematic item analysis to ensure the availability of a standardized, valid, and reliable item bank. Implementing such procedures can support more accurate and objective assessment processes in technician certification, ultimately improving the quality of competency measurement. Abstrak Analisis butir soal merupakan proses untuk mengevaluasi kualitas setiap item dalam suatu tes agar mampu mengukur kemampuan peserta secara akurat. Berdasarkan observasi di PT SGMW Motor Indonesia, analisis butir soal pada sertifikasi teknisi Level 0 – Apprentice 2023 belum dilaksanakan, yang terlihat dari minimnya perhatian terhadap tingkat kesulitan soal. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif, dengan subjek peserta sertifikasi dan objek berupa soal ujian teknisi Level 0 – Apprentice. Data dikumpulkan melalui dokumentasi dan dianalisis menggunakan Microsoft Excel untuk menilai validitas, reliabilitas, tingkat kesulitan, daya pembeda, serta efektivitas pengecoh. Hasil penelitian menunjukkan bahwa dari 250 soal yang dikaji, 34% (84 soal) masuk kategori ditolak, 32% (80 soal) perlu direvisi, dan 34% (86 soal) dapat disimpan sebagai soal berkualitas. Temuan ini menegaskan pentingnya pelaksanaan analisis butir soal secara berkala untuk memastikan tersedianya bank soal yang valid, reliabel, serta sesuai standar evaluasi pembelajaran, sehingga proses sertifikasi mampu menghasilkan pengukuran kompetensi teknisi yang lebih objektif dan tepat sasaran.